Impact of Infrastructure and Government Support on Corn Production in Indonesia: A Case on Integrated Crop Management Farmer Field School - Kariyasa, I Ketut (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2011)
EnglishCorn is the second most important food crop after rice in Indonesia. It is a versatile crop and also the second biggest contributor to crop sectorâs GDP. However, domestic supply of corn has not been able to meet demand satisfactorily. To address this problem, the Indonesian government since 2009 has implemented the Farmersâ Field School of Integrated Crop Management (ICM-FFS) program on corn production. But, the success of this program is also dependent on the infrastructure available and government support where the program is implemented. The study found that good infrastructure and government support increased ICM-FFS corn farms productivity by 9.81%, with 5.62% as a direct impact and 4.19% as an indirect impact. The production difference due to infrastructure and government support was contributed by pure yield effect (52.85%) and pure area effect (42.73%). The income per corn farmer differential of Rp 1.50 million arising from good infrastructure and government support was attributed to yield effect (36.79%), area effect (29.75%), and price effect (25.42%).Â Road conditions and market infrastructure improvement, government support enhancement and provision of competitive input and output markets could be considered as policy directions to improve corn production in Indonesia.ABSTRAKDi Indonesia, jagung merupakan komoditas terpenting kedua setelah padi. Selain mempunyai banyak fungsi, jagung juga sebagai penyumbang terbesar kedua terhadap PDB sektor tanaman pangan. Namun demikian, produksi jagung dalam negeri belum mampu memenuhi permintaannya secara memuaskan. Untuk mengatasi permasalahan ini, Pemerintah Indonesia sejak 2009 melaksanakan SLPTT jagung. Namun demikian, keberhasilan program ini juga ditentukan oleh ketersediaan infrastruktur dan dukungan pemerintah dimana program ini dikembangan. Hasil penelitian menunjukkan bahwa infrastruktur dan dukungan pemerintah yang bagus mampu meningkatkan produktivitas SLPTT jagung sebesar 9,81persen dimana 5,62 persensebagai dampak langsung dan 4,19 persen sebagai dampak tidak langsung dariÂ infrastruktur dan dukungan pemerintah. Mereka juga mampu meningkatkan produksi jagung, dimana 52,85 persen berasal dari kontribusi produktivitas dan 42,73 persen berasal dari kontribusi lahan. Selain itu, mereka meningkatkan pendapatan petani sekitar Rp 1,5 juta, dimana masing-masing 36,79, 29,75, dan 25,42 persen berasal dari kontribusi produktivitas, lahan, dan harga jagung. Kondisi jalan dan dukungan pemerintah yang semakin baik serta penyediaan pasar input dan output yang lebih bersaing diharapkan mampu meningkatkan kinerja SLPTT jagung ke depan.